Applications of nanomaterials with enzyme-like activity for the detection of phytochemicals and hazardous substances in plant samples - Lei Xu; Mao-Ling Luo; Jing-Jing Dai; Huan Zhu; Peng Li; Dan Wang; Feng-Qing Yang (BMC, 2024)
Abstract Plants such as herbs, vegetables, fruits, and cereals are closely related to human life. Developing effective testing methods to ensure their safety and quantify their active components are of significant importance. Recently, nanomaterials with enzyme-like activity (known as nanozymes) have been widely developed in various assays, including colorimetric, fluorescence, chemiluminescence, and electrochemical analysis. This review presents the latest advances in analyzing phytochemicals and hazardous substances in plant samples based on nanozymes, including some active ingredients, organophosphorus pesticides, heavy metal ions, and mycotoxins. Additionally, the current shortcomings and challenges of the actual sample analysis were discussed.